Heart rate, heart rate variability and inflammatory biomarkers among young and healthy adults. (2nd January 2017) - Aeschbacher, Stefanie; Schoen, Tobias; Dörig, Laura; Kreuzmann, Rahel; Neuhauser, Charlotte; Schmidt-Trucksäss, Arno; Probst-Hensch, Nicole M.; Risch, Martin; Risch, Lorenz; Conen, David
Abstract: Background: Heart rate (HR), heart rate variability (HRV), and inflammation are all associated with cardiovascular morbidity and mortality. The aim of this study was to assess potential interrelationships between these parameters in a young and healthy population. Methods: Healthy individuals aged 25–41 years were included in a prospective population-based study. All participants underwent 24-h electrocardiography using a validated device. The standard deviation of all normal RR intervals (SDNN) was pre-defined as the main HRV outcome variable. High-sensitivity C-reactive protein (hs-CRP), total leukocyte (LC) count and LC subtypes were obtained from venous blood samples. Results: A total of 2064 participants (47% men, 37 years) were included in this analysis. In multivariable linear regression analyses using SDNN as the outcome variable, β-coefficients (95% confidence intervals) per 1 standard deviation (SD) increase on the log-scale were −0.11 (−0.16; −0.07), p < .0001 for hs-CRP, −0.13 (−0.17; −0.09), p < .0001 for total LC count, −0.12 (−0.16; −0.08), p < .0001 for neutrophils, −0.04 (−0.09; 0.00), p = .05 for lymphocytes and −0.08 (−0.09; −0.02), p = .005 for monocytes. There were positive relationships between resting and ambulatory HR and inflammatory biomarkers, except for lymphocytes. Conclusion: In this large cohort of young and healthy adults, inflammatory parameters were strongly associated with increased HR and decreased HRV, suggesting an important interaction between inflammatory pathways and the autonomic nervous system. Key message: Inflammatory biomarkers, such as high-sensitivity C-reactive protein and leukocyte cell count with its subtypes were inversely associated with HRV and positively associated with HR. Our findings suggest important interrelationships between inflammatory pathways and the ANS.